A phenomenological study of a Z' Boson in the jj+ll channel with an intermediate heavy neutrino state using vector boson fusion processes (2017)
"This document presents, the most simple, non Supersymmetric, extension of the Standard Model (SM) of Particle Physics. The document starts with brief summary of Classical Mechanics, from the Newtonian formulation to the Lagrangian and Hamiltonian formulation for particles and fields. In addition, the relativistic formulation of quantum mechanics is studied, making an emphasis in the Klein-Gordon and the Dirac equations and how their solutions describe quantum fields. Then, a mathematical interlude, which introduces the concept of group and Lie group, is made to understand how symmetries in physics merge as representations of the action of Lie groups over a certain set. Moreover, the study of symmetries of the weak, electromagnetic and strong interactions yields to the introduction of interaction fields, building the SM. After introducing the SM of particle physics, the concept of Majorana field is introduced, as an alternate formulation of a Dirac field, to explain how the existence of these fields can explain neutrino masses by an extra phase symmetry in the electroweak sector. This new symmetry, implies that a new neutral gauge boson, the Z-, must be introduced such that it can explain neutrino masses by a Type 1 Seesaw mechanism. Finally, the theoretical calculations related to production cross sections of a Z- boson in pp collisions, either in the Drell-Yann and the Vector Boson Fusion sectors, are shown."--Tomado del Formato de Documento de Grado